Inequality in iron and folic acid consumption and dietary diversity in pregnant women following exposure to maternal nutrition interventions in three low- and middle-income countries - Deepali Godha; Sandra Remancus; Tina Sanghvi (Cambridge University Press, 2024)
Abstract Objective: Research is available on improved coverage and practices from several large-scale maternal nutrition programmes, but not much is known on change in inequalities. This study analyses wealth and education inequality using Erreygers and Concentration indices for four indicators: adequate iron and folic acid (IFA) consumption, women's dietary diversity, and counselling on IFA and dietary diversity. Design: A pre-test-post-test, control group design. Setting: Maternal nutrition intervention programmes conducted in Bangladesh, Burkina Faso and Ethiopia during 2015-2022. Participants: Recently delivered women (RDW) and pregnant women (PW). Results: Statistically significant reductions in education inequality were observed for adequate IFA consumption, counselling on IFA and dietary diversity in intervention areas of Bangladesh and for adequate IFA consumption in intervention areas of Burkina Faso. A significant decrease in wealth inequality was observed for adequate IFA consumption in the intervention areas of Bangladesh, whereas a significant increase was observed in the non-intervention areas for counselling on IFA in Ethiopia and for dietary diversity in Burkina Faso. Conclusion: The results can be attributed to the extensive delivery system at community level in Bangladesh and being predominantly facility-based in Burkina Faso and Ethiopia. COVID-19 disruptions (in Burkina Faso and Ethiopia) and indicator choice also had a role in the results. The main takeaways for nutrition programmes are as follows: (a) assessing inequality issues through formative studies during designing, (b) monitoring inequality indicators during implementation, (c) diligently addressing inequality through targeted interventions, setting aside resources and motivating frontline workers to reduce disparities and (d) making inequality analysis a routine part of impact evaluations.